ВІМС дослiдження поверхнi гiдридоутворюючого сплаву TiFe - Litvinov, V. A.; Okseniuk, I. I.; Shevchenko, D. I.; Koppe, V. T.; Bobkov, V. V.; Chornous, V. M. (Publishing house "Academperiodika", 2018)
The surfaces of specimens of TiFe hydrogen storage alloy have been studied with the use of secondary ion mass spectrometry. Even after the annealing of a specimen in vacuum and its cleaning with an ion beam, a substantial part of its surface is shown to remain coated with a bulky layer composed of oxides, hydrides, hydroxides, and carbides. This layer has to be taken into account when considering problems dealing with the kinetic parameters of hydride formation.